Perbedaan Daya Hambat Ekstrak Daun Kepuh (Sterculia foetida L.) dan Jarak Pagar (Jatropha curcas L.) terhadap Pertumbuhan Propionibacterium acne - Joko Waluyo (saintifika, 2014)
Acne is a kind of disease caused by Propionibacterium acne bacteria. Acne (Acne vulgaris) is a skin disease with chronicle inflammation of follicles polisebacea which generally occurs in adolescence. Treatment commonly used Medicinal Chemicals with high levels that can be harmful to the body. Alternatives that can be used as a substitute for Medicinal Chemicals is medicinal herbal of plant. Plants that can be used as herbal medicines are Kepuh and Jatropha. Kepuh contain triterpenoid, Jatropha contains alkaloid, tannin, saponin and flavonoid. The compounds have the potential as an antibacterial. This research is an experimental research laboratory that uses the diffusion method. Concentration used is 1%, 3%, 5%, 7% and 9%. Based on the results of statistical tests ANOVA difference of Kepuh leaf extract and Jatropha forPropionibacterium acne showed significant differences among treatments with significance value of 0.001. Minimum Inhibitory Concentration (MIC) Kepuh leaf extract that can inhibit the Propionibacterium acne is 3% of 0.7 mm, while the MIC of Jatropha leaves extracts for Propionibacterium acne is 4% of 0.38 mm.